AVANCES EN LA IDENTIFICACION DE MINERALES CONTAMINANTES EN SUELOS DE LA RESERVA NACIONAL DE JUNIN - Fabián S., Julio (2005)
The samples in study are located, in the National Reserve of Junín located in the provinces and regions of Junín and Paseo, in the central mountain range of Peru, between 10°54 11 and 11°08 11 South Latitude and 76°00 " and 76°15 11 Latitude the 4 081,60 West to m.s.n.m. The great ecological value that it has by the great biodiversity in species that lodges in its three main ecological communities (terrestrial, aquatic and omithological); besides to serve as hydric regulator for the hydroelectric power station of the Mantaro made that an study of soils from this place being very important. The used analytical techniques for the mineralogical characterization, were the X-rays Diffraction , X-rays fluorescence and spectroscopy Mossbauer of transmision as a technical of complementary analyses. Also were made physical and chemical procedures to measure the cation interchange, pH, determination of percentage of Organic Matter, percentage of salinity and electric conductivity. To eliminate the high concentration of iron in soils it was used the DCB (dithionite citrate bicarbonate) treatment in sorne cases. The Difractograms of rays X of the samples treated by DCB gives the presence of different types from clays, iron oxides and minerals of difficult appearance in a common soil. The analyses done with X-rays fluorescence indicated the presence of rubidium, tungsten, calcium, iron, nickel, cooper, zinc, gold and zirconium. The minerals identified by Mossbauer spectroscopy at room temperature showed the presence, in greater proportion, of paramagnetic iron, but also there is magnetic iron. The paramagnetic iron indicates two sites and the magnetic iron apparently shows a distribution of sites.